Comprehensive analysis of geometrical parameters of crosshatched texture for enhanced tribological performance under biological environment. (February 2021) - Kashyap, V; Ramkumar, P
This study optimizes the texture geometry by investigating the individual effect of texture depth and area density of cross hatched texture to improve the tribological performance of hip implant at normal walking speed. Texture width was selected conforming to Hertzian contact of Ti6Al4V/ultrahigh molecular weight polyethylene tribo-pair. Crosshatched textures with different depths and area densities were fabricated on polished Ti6Al4V blocks using laser surface texturing technique. Tribology tests were carried out for different loads under bio-lubricated condition. Result shows significant influence of texture depth and area density for better tribological performance of the tribo-pair. Nearly 50% friction reduction and 15 times reduction in wear obtained for 5 µm depth at 25% area density. Surface morphology of worn-out pins showed abrasion wear mechanism.